BYPRODUCTS OF AQUACULTURE PROCESSES: DEVELOPMENT AND PROSPECTIVE USES. REVIEW - Leidy Maritza SIERRA LOPERA; Cindy Tatiana SEPÚLVEDA RINCÓN; Priscilla VÁSQUEZ MAZO; Omar Alfredo FIGUEROA MORENO; José Edgar ZAPATA MONTOYA (Vitae)
ABSTRACT Background: Growing aquaculture production around the world generates an important environmental impact because of its waste volume, which reaches nearly 60%. These byproducts have important levels of protein and lipids that can be revaluated to obtain products that are of interest to the pharmaceutical and food industries such as bioactive peptides and functional properties. Recently, technologies have been applied to the isolation and purification of bioactive peptides according to their molecular weight, such as membrane separation techniques and chromatography. Currently, there are commercial products from fish protein hydrolysates that can be used in nutritional and pharmaceutical applications as a source of amino acids with different physiological functions. Objective: Give information on aquaculture byproducts, hydrolysis methods, methods of purification, bioactive peptides and functional properties and nutritional supplements. Methods: Science Direct, Springer Link, Wiley Online Library, and Scopus were reviewed using the keywords aquaculture products, protein hydrolysis, bioactive peptides, functional properties. For the selection of the articles, the year of publication, the language, the methodology used and the trajectory of the authors were taken into account. Conclusions: This review is a brief description of the use of aquaculture byproducts using different types of hydrolysis process and their multiple applications on several industries.